2017
DOI: 10.1038/nmicrobiol.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Zika virus epitopes reveals immunodominant and protective roles for dengue virus cross-reactive CD8+ T cells

Abstract: CD8+ T cells play an important role in controlling Flavivirus infection, including Zika virus (ZIKV). Here, we have identified 25 HLA-B*0702-restricted epitopes and 1 HLA-A*0101-restricted epitope using interferon (IFN)-γ enzyme-linked immunospot (ELISPOT) and intracellular cytokine staining (ICS) in ZIKV-infected IFN-α/β receptor-deficient HLA transgenic mice. The cross-reactivity of ZIKV epitopes to dengue virus (DENV) was tested using IFN-γ-ELISPOT and IFN-γ-ICS on CD8+ T cells from DENV-infected mice, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
184
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(199 citation statements)
references
References 49 publications
11
184
0
4
Order By: Relevance
“…These epitopes represent the first mapping of DENV/ZIKV cross-reactive epitopes in humans, and in most cases the cross-reactivity could be explained by identity or high similarity to sequences previously identified in one or more DENV serotypes. This finding was predicted by previous analysis conducted by the IEDB analysis resource (6) and by a recent study utilizing HLA transgenic mice (29). Nonetheless, identification of specific sequences here allows for a comprehensive assessment of whether the cross-reactivity is focused on regions that are highly conserved.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These epitopes represent the first mapping of DENV/ZIKV cross-reactive epitopes in humans, and in most cases the cross-reactivity could be explained by identity or high similarity to sequences previously identified in one or more DENV serotypes. This finding was predicted by previous analysis conducted by the IEDB analysis resource (6) and by a recent study utilizing HLA transgenic mice (29). Nonetheless, identification of specific sequences here allows for a comprehensive assessment of whether the cross-reactivity is focused on regions that are highly conserved.…”
Section: Discussionsupporting
confidence: 77%
“…This is the first evidence in humans that previous exposure to dengue virus can influence subsequent infection with ZIKV by mounting a cross-reactive memory T cell response against ZIKV. Recent data in HLA transgenic mice demonstrated that ZIKV challenge following immunization of mice with ZIKV-specific and ZIKV/DENV cross-reactive epitopes elicited CD8 ϩ T cell responses that reduced infectious ZIKV levels, and CD8 ϩ T cell depletions confirmed that CD8 ϩ T cells mediated this protection (29). In addition, a recent paper has shown that Zika virus pathogenesis in rhesus macaques is unaffected by preexisting immunity to dengue virus (33).…”
Section: Discussionmentioning
confidence: 97%
“…Most of these studies focused on the cross talk of neutralizing antibodies between ZIKV and DENV and the structural basis for such cross-reactivity. A very recent study of ZIKV reported that DENV-specific CD8 ϩ T cell epitopes were cross-reactive to ZIKV, and this was also demonstrated in Ifnar1 Ϫ/Ϫ mice (11). In the present study, we sought to investigate whether such cross-reactivity of CD8 ϩ T cells can be observed in WT mice.…”
Section: Resultsmentioning
confidence: 81%
“…A recent publication showed that ZIKV/DENV cross-reactive peptides immunization provided protection against ZIKV infection (11). However, whether the cross talk mediated by CD8 ϩ T cells post-ZIKV infection could prevent DENV infection remains unclear.…”
Section: Role Of the Cd8 ؉ T Cell Response During Zikv Infectionmentioning
confidence: 99%
See 1 more Smart Citation